2022
DOI: 10.1177/20503121221092338
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and associated factors towards palliative care among nurses in Ethiopia: A systematic review and meta-analysis

Abstract: Palliative care is a holistic care that emphasises on relieving pain and other symptoms of a critical illness, irrespective of age, diagnosis, or stage of illness. It improves the quality of life of the individual. Since nurses spend the longest time with patients, they are the heart of the palliative care team who deliver high standards of care. This study was intended to assess the pooled prevalence of knowledge and associated factors towards palliative care among nurses in Ethiopia. During this study, a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Even if significant efforts have been made towards palliative care practice, an interdisciplinary and integrated approach to palliative care is still lacking. 13 So far, regarding palliative care, studies conducted in Ethiopia have emphasized on knowledge of nurses towards palliative care, [15][16][17] and some studies have assessed the practice of palliative care in specific areas of the country, 18 limiting the generalizability of these studies. For instance, a study in Shire town, Tigray Region, northern Ethiopia, has shown the practice of palliative care at public health facilities in one town.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if significant efforts have been made towards palliative care practice, an interdisciplinary and integrated approach to palliative care is still lacking. 13 So far, regarding palliative care, studies conducted in Ethiopia have emphasized on knowledge of nurses towards palliative care, [15][16][17] and some studies have assessed the practice of palliative care in specific areas of the country, 18 limiting the generalizability of these studies. For instance, a study in Shire town, Tigray Region, northern Ethiopia, has shown the practice of palliative care at public health facilities in one town.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these factors were not well studied in previously conducted studies as these studies were inconclusive. [15][16][17][18] In summary, the purpose of this study was to identify nurses' palliative care practice level and factors associated with palliative care in chronic care units of selected tertiary hospitals in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%